Parents' concerns and attitudes towards school reopening during COVID-19 pandemic: a cross-sectional survey-Tripoli, Libya, 2021. Issue 1 (31st December 2022) - Jallul, Mwada; Elgriw, Nada; Eltaib, Farag I; Al Dwigen, Samira M; Elfallah, Asma; Elgheriani, Hajer M; Atwear, Wafeya S; Milad, Mohamed Burid; Alhudiri, Inas M; Elzagheid, Adam
ABSTRACT: The issue of school reopening has raised several concerns; therefore, the parent's opinion is essential to consider. This study aimed to evaluate the parent's attitudes and concerns toward school reopening in the COVID-19 era. A cross-sectional survey was performed using in-person self-administered questionnaires, the data was collected in the period between January and April 2021 covering parents' concerns and attitudes toward school reopening. A total of 402 parents participated in the survey. Analysis showed that 56.7% of parents have agreed with school reopening, but 54% have raised some legitimate concerns. Importantly, there was a strong correlation between parents' opinions towards school reopening and their level of education, and their concerns about their children's safety if the school was reopened. Despite parents' concerns, it does seem that slightly over half were in favour of school reopening and would send their children to school only if the schools did apply strict precautions and restriction measures. Sharing parents' views toward school reopening with school leaders and decision-makers is important to assess the feasibility and effectiveness of return to schools and to improve existing prevention programs.